Applied Statistics for Social and Management Sciences - Miah, Abdul Quader; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book addresses the application of statistical techniques and methods across a wide range of disciplines. While its main focus is on the application of statistical methods, theoretical aspects are also provided as fundamental background information. It offers a systematic interpretation of results often discovered in general descriptions of methods and techniques such as linear and non-linear regression. SPSS is also used in all the application aspects. The presentation of data in the form of tables and graphs throughout the book not only guides users, but also explains the statistical application and assists readers in interpreting important features. The analysis of statistical data is presented consistently throughout the text. Academic researchers, practitioners and other users who work with statistical data will benefit from reading Applied Statistics for Social and Management Sciences. .
1: Basics -- 2: Presentation of Statistical Data -- 3: Descriptive Statistics -- 4: Probability Theory -- 5: Probability Distributions -- 6: Statistical Inference -- 7: Hypothesis Testing -- 8: The Chi-Square Test -- 9: Non-Parametric Test -- 10: Correlation -- 11: Simple Regression -- 12: Multiple Regression -- 13: Sampling Theory -- 14: Determination of Sample Size -- 15: Index Numbers -- 16: Analysis of Financial Data -- 17: Experimental Design -- 18: Statistical Quality Control -- 19: Summary for Hypothesis Testing.
Keywords: Statistics; Statistics; Statistics for Social Science, Behavorial Science, Education, Public Policy, and Law; Statistics for Business/Economics/Mathematical Finance/Insurance.; Statistical Theory and Methods; Electronic books